Improvement of the vertical “scatter degree” method and its application in evaluating water environmental carrying capacity - Zhi Hong, Zheng; Yan Xu, Yu (Tecnología y ciencias del agua, 2017)
Zheng, Z. H., & Yu, Y. X. (March-April, 2017). Improvement of the vertical “scatter degree” method and its application in evaluating water environmental carrying capacity. Water Technology and Sciences (in Spanish), 8(2), 71-76. The “scatter degree” method is an objective evaluation method based on a “difference drive*”. However, it is currently perceived as incapable of properly reflecting the subjective information of the evaluator. In order to reflect the objective law of raw data and assist decision-makers to control major factors of the water environmental carrying capacity (WECC), this paper proposes a method to process the weight of the indicator by combining the analytic hierarchy process (AHP) and the vertical “scatter degree” method. The computing results of this improved method are virtually identical to those of the old method, but the former is more scientific and reliable.